Perceived Managerial and Leadership Effectiveness Within Turkish Public Sector Hospitals - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
The main purpose of this study is to report the results of a study of managerial and leadership effectiveness carried out within Turkish public sector hospitals. 'Effective' and 'least effective/ineffective' manager and managerial leader behavior, as observed by managerial and non-managerial employees were collected using the critical incident technique. These critical incidents were then content analyzed to identify a smaller number of discrete behavioral statements and criteria of effectiveness. (C) 2013 The Authors. Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: managerial and leadership effectiveness; cross-nation research; healthcare management; BEHAVIORS